Relationship between stressful life events and parental verbal aggression, and depressive symptoms in Malaysian adolescents, with sex and parental warmth as moderators - May, Barra Sharisse (2017)
Depression is a serious mental health problem amongst Malaysian adolescents. There is a wide range of detrimental effects of depression such as smoking, suicide, impaired functioning, financial costs, and the possibility of recurrence in later years. Previous studies have found that stressful life events (SLE) and parental verbal aggression predict depression in adolescents. The relationships between these risk factors and depression have also been found to differ for females and males. Additionally, parental warmth has been studied as a factor that decreases the negative effect of stressful life events and parental verbal aggression. However, within the Malaysian context, there is lack of empirical data on the relationships among these variables. As such, using a secondary data source, the current study conducted a quantitative investigation of the impact of stressful life events and parental verbal aggression on depressive symptoms. Additionally, this study examined the moderating roles of parental warmth and sex. The sample consisted of 1092 secondary-school adolescents aged between 13 and 19 years (mean = 15.32) who were recruited using probability proportional to size (PPS) cluster sampling from the states of Johor, Kelantan, Kuala Lumpur, and Pulau Pinang. For hypotheses testing, binary logistic regression was performed using SPSS (v. 20). Results of this study revealed that the prevalence of depressive symptoms among Malaysian adolescents was 57%. In the univariable analyses, stressful life events, paternal verbal aggression (PVA), and maternal verbal aggression (MVA) were all unique predictors of depression. However, in the multivariable model, paternal verbal aggression was no longer a significant predictor of depression, controlling for all other variables in the regression equation. Moreover, girls showed a higher probability of depression than boys with increasing levels of stressful life events. Low levels of paternal warmth (PW) resulted in increasing probability of depression as paternal verbal aggression increased. On the other hand, high levels of paternal warmth elicited decreasing probability of depression even when paternal verbal aggression increased. Furthermore, even at high levels of paternal warmth, the probability of depression continued to rise as maternal verbal aggression increased. In contrast, maternal warmth (MW) did not moderate any of the hypothesized associations between the risk factors and depression. In conclusion, stressful life events and maternal verbal aggression had robust main effects on depression, sex was a significant moderator of the relationship between stressful life events and depression, and paternal warmth was generally a factor that reduced the negative effects of paternal verbal aggression. These findings imply that harsh parenting employed by the mother has a more harmful effect on the adolescent’s mental health than that of the father; whereas positive parenting by the father may be more important in safeguarding adolescents from developing depression than that of the mother. Moreover, findings from this study may be useful in improving the mental health programs of the country.